Head and neck lymphomas – a retrospective ten-year observation - Niemiec, Marcelina; Stryjewska-Makuch, Grażyna; Janik, Małgorzata; Kolebacz, Bogdan; Lisowska, Grażyna; Ścierski, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2017)
Aim of the study : Lymphomas are a heterogeneous group of tumours of lymphoid tissue in which there is an abnormal proliferation of cells of the lymphatic system. The literature notes a gradual increase in the incidence of this type of cancer in the whole population. The aim of the study was to evaluate whether the above tendency occurs in the head and neck area. Material and methods : In the years 2005–2014, at the Otolaryngology and Laryngological Oncology Department of the Upper Silesian Medical Centre in Katowice, 77 cases of lymphoma were recorded, 58 of which were analysed in terms of location, histological type, age and sex of the patient, and the presence of risk factors. Results : The vast majority of them were non-Hodgkin’s lymphomas (NHL) – 67.53%. Hodgkin’s lymphomas (HL) accounted for only a small fraction of diagnoses (7.79%). In terms of histopathological types, in most cases of NHL, there occurred diffuse large B-cell lymphomas (DLBCL) – 51.92%. The most common location was the lymph nodes, representing the location of the primary lesion in more than half of the cases. As regards the extranodal location, the Waldeyer ring dominated (54.54%) along with the palatal tonsil (40.90%). There has been a significant upward trend, especially in the incidence of NHL.